Role of Emblica officinalis (amla) in the prophylaxis of hepatic injury by carbon tetrachloride (CCl4) in albino rats - Deori, Chinmoyee; Das, Swarnamoni; Bordoloi, Sushanta Kumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective of the study was to evaluate the hepatoprotective activity of fruits extract of Emblica officinalis on carbon tetrachloride induced hepatotoxicity in Albino rats. Liver is vulnerable to wide variety of metabolic, toxic, microbial, circulatory and neoplastic insults. The dominant primary diseases of the liver are viral hepatitis, alcoholic liver disease and hepatocellular carcinoma. Due to absence of reliable drugs management of liver ailments in the modern medicine, plants and natural products are providing to be good hepatoprotectants as evident from voluminous published work on their hepatoprotective potentials. Methods: The required amount of fresh fruits of Emblica officinalis was collected and dried at room temperature. The dried fruit ground into powdered and was prepared by percolation method using 95% ethanol. Acute oral toxicity test of the fruits extract was performed as per OECD 423 guidelines. Carbon tetrachloride was used as the hepatotoxin. Silymarin suspension 100mg was used as a standard drug in this study. Results: The study was carried out with an attempt to evaluate the hepatoprotective activity of Emblica officinalis in carbon tetrachloride induced hepatic injury in albino rats. The results were analysed by using one way ANOVA followed by Dunnett’s test and (p <0.05) was considered significant. Conclusions: The present study shows that the Emblica officinalis has significant hepatoprotective activity in rats with carbon tetrachloride induced liver injury. Emblica officinalis is a commonly used traditional herb, which is safe, cost effective and grows widely in India and used by different ethnic groups for various diseases. That is why Emblica officinalis, a commonly used natural herb, deserve further consideration in order to establish its potential as safe economical hepatoprotective agent.